Identification of Gonadulin and Insulin-Like Growth Factor From Migratory Locusts and Their Importance in Reproduction in Locusta migratoria - Veenstra, Jan A.; Leyria, Jimena; Orchard, Ian; Lange, Angela B. (Frontiers in Endocrinology, 2021)
Many insect species have several genes coding for insulin-related peptides (IRPs), but so far only a single IRP gene has been identified in migratory locusts. Here, we report and characterize two other genes coding for peptides that are related to insulin, namely gonadulin and arthropod insulin-like growth factor (aIGF); peptides postulated to be orthologs of Drosophila melanogaster insulin-like peptides 8 and 6 respectively. In Locusta migratoria the aIGF transcript is expressed in multiple tissues as was previously reported for IRP in both L. migratoria and Schistocerca gregaria, but there are significant differences in expression patterns between the two species. The gonadulin transcript, however, seems specific to the ovary, whereas its putative receptor transcript is expressed most abundantly in the ovary, fat body and the central nervous system. Since the central nervous system-fat body-ovary axis is essential for successful reproduction, we studied the influence of gonadulin on vitellogenesis and oocyte growth. A reduction in the gonadulin transcript (via RNA interference) led to a significant reduction in vitellogenin mRNA levels in the fat body and a strong oocyte growth inhibition, thus suggesting an important role for gonadulin in reproduction in this species.